2020
DOI: 10.1007/s10903-020-01104-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of COVID-19 on Recently Resettled Refugee Populations in the United States and Canada: Perspectives of Refugee Healthcare Providers

Abstract: Recently resettled refugee populations may be at greater risk for exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a virus that causes coronavirus 2019 (COVID-19), and face unique challenges in following recommendations to protect their health. Several factors place resettled refugees at elevated risk for exposure to persons with COVID-19 or increased severity of COVID-19: being more likely to experience poverty and live in crowded housing, being employed in less protected, service-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 7 publications
1
61
0
1
Order By: Relevance
“…With routine services closed due to the pandemic, concerns have been raised that migrants have struggled to navigate the new systems ( Doctors of the World 2020 , Valeriani et al, 2020 , Esegbona-Adeigbe, 2020 , Nobody Left Outside 2020 ) and it has exacerbated migrants’ exclusion from health services ( Desai and Samari, 2020 , Santos et al, 2020 , Aragona et al, 2020 , Clarke et al, 2020 , Devillanova et al, 2020 ). Migrants may experience challenges in accessing healthcare remotely ( Doctors of the World 2020 , Brickhill-Atkinson and Hauck, 2020 , Page et al, 2020 , Langellier, 2020 , Wernly et al, 2020 ); however, telemedicine may also offer opportunities that need to be further explored in these populations ( Warner et al, 2020 , Green et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…With routine services closed due to the pandemic, concerns have been raised that migrants have struggled to navigate the new systems ( Doctors of the World 2020 , Valeriani et al, 2020 , Esegbona-Adeigbe, 2020 , Nobody Left Outside 2020 ) and it has exacerbated migrants’ exclusion from health services ( Desai and Samari, 2020 , Santos et al, 2020 , Aragona et al, 2020 , Clarke et al, 2020 , Devillanova et al, 2020 ). Migrants may experience challenges in accessing healthcare remotely ( Doctors of the World 2020 , Brickhill-Atkinson and Hauck, 2020 , Page et al, 2020 , Langellier, 2020 , Wernly et al, 2020 ); however, telemedicine may also offer opportunities that need to be further explored in these populations ( Warner et al, 2020 , Green et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies have demonstrated that age, gender, socioeconomic deprivation, ethnicity could be predictive demographic and social risk factors for COVID-19. Moreover, also hypertension, diabetes and obesity are underlying health conditions that can increase the risk of the disease [31]. The interplay of this underlying conditions and the risk of contracting COVID-19 infection through work, is a multifocal concern [32].…”
Section: Discussionmentioning
confidence: 99%
“…demographic data and characteristics of the worker (question from 1 to 8) -relevant work information (9-13) -heat-exposure-related questions and information about PPE' usage at work (14-20) -worker's adaptation to heat stress and behavioral with PPE (21-27) -worker's knowledge about thermal stress and attitudes towards the PPE's use (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) A 5-point Likert scale (1 for strongly disagree and 5 for strongly agree) was used for questions from 28 to 46 concerning the worker's knowledge about thermal stress and attitudes towards the PPE's use.…”
Section: Survey Developmentmentioning
confidence: 99%
“… 8 Third, public health messaging should target refugee communities through culturally sensitive and linguistically appropriate resources, and the use of medical interpreters. 31 …”
Section: Recommendations and Limitationsmentioning
confidence: 99%